1979
DOI: 10.1073/pnas.76.8.3760
|View full text |Cite
|
Sign up to set email alerts
|

Nicking-closing activity associated with bacteriophage lambda int gene product.

Abstract: Integrative recombination of bacteriophage X requires the action of the protein Int, the product of the phage int gene. In this paper we show that highly purified Int relaxes supercoiled DNA. The association of this nicking-closing activity with Int is shown by: (i) the cosedimentation o nicking-closing and recombination activities of purified Int, (ii) the parallel inactivation of the two activities in purified Int by both heat and a specific antiserum, and (iii) the alteration of both activities in crude ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(55 citation statements)
references
References 23 publications
2
53
0
Order By: Relevance
“…One model, but not necessarily the only model, consistent with this constraint is one in which the reaction proceeds through close association of the four strands of the two core regions, followed by strand exchange catalyzed by a topoisomerase activity of FLP protein. Such a mechanism has been previously proposed for int-catalyzed phage lambda integration (10,14) and for cre-catalyzed recombination between loxP sites of phage P1 (8). This mechanism is also consistent with the behavior of FLP protein in vitro (la, 6b, 19).…”
Section: Discussionsupporting
confidence: 71%
“…One model, but not necessarily the only model, consistent with this constraint is one in which the reaction proceeds through close association of the four strands of the two core regions, followed by strand exchange catalyzed by a topoisomerase activity of FLP protein. Such a mechanism has been previously proposed for int-catalyzed phage lambda integration (10,14) and for cre-catalyzed recombination between loxP sites of phage P1 (8). This mechanism is also consistent with the behavior of FLP protein in vitro (la, 6b, 19).…”
Section: Discussionsupporting
confidence: 71%
“…In the Cre lox system (8) and in the bacteriophage X integrase system (9, 10), there is genetic evidence that site-specific recombination stimulates gene conversion of nearby markers. In both these systems, studies of linking number changes in DNA during recombination (11, 12) and the ability of the recombinases to act as type I topoisomerases (13,14) are consistent with a model of sequential single-stranded breaks and exchanges. In addition, artificial Holliday intermediates have been formed using the DNA ofthe bacteriophage X att site, and it has been demonstrated that such structures are acted upon by the recombinase Int (15).…”
mentioning
confidence: 67%
“…Type I topoisomerase, first described in prokaryotes by Wang (1971) and in eukaryotes by Champoux and Dulbecco (1972) and later characterized by Keller (1975a, b), change the linking number in steps of one. Although their biological function is not completely defined , this class of topoisomerase has been implicated in transcriptional (Akrigg and Cook 1980;Dynan and Burgess 1981;Sternglanz et al 1981;Weisbrod 1982;Fleischmann et al 1984 ;Gilmour et al 1986;Shastry 1986) as well as in recombinational and replicational (Kikuchi and Nash 1979 ;Sternglanz et al 1981 ; also see Gellert 1981 ;Bullock et al 1985 ;Zeng et al 1985) events. J n higher eukaryotes topoisomerase I is enriched in the nucleolus (Fleischmann et al 1984;Muller et al 1985) and may play a role in transcription of supercoiled rDNA in vitro (Garg et al 1987).…”
Section: Introductionmentioning
confidence: 99%